Prolanis Health Talk Education for Hypertension and Diabetes Mellitus Communities: A Community Service Program Approach - Siti Rahmi; Agus Sugiharto; Retno Asti Werdhani; Dian Kusumadewi; Vican Sefiany Koloi (Poltekita: Jurnal Pengabdian Masyarakat, 2026)
Two non-communicable diseases that rank third in terms of mortality and are becoming more common in Indonesia are hypertension (HT) and diabetes mellitus (DM). The Chronic Disease Management Program (Prolanis), which aims to maintain the health of individuals with HT and DM, was introduced by the government and the National Health Care Security (BPJS) in response. Prolanis is intended for patients at Primary Health Care Facilities diagnosed with HT and DM. Nonetheless, participation in the Prolanis program remains relatively low. This program aims to increase the knowledge and involvement of HT and DM patients in Prolanis at the Annisa Dua Clinic in Citereup, Bogor City, by using Health Talk Education. The activity's outcomes demonstrated that participants' attitudes and understanding of the significance of participating in Prolanis had increased. Participants also felt more understanding and motivated to participate in activities and contribute to Prolanis. There was high participant satisfaction with this community service program. Participation in Prolanis can be increased through education about the importance of participating in community-based Prolanis related to the community. Of course, collaboration from various parties is needed to achieve Prolanis's goals.